Using a shared L1 to reduce cognitive overload and anxiety levels in the L2 classroom. Issue 3 (3rd July 2017) - Bruen, Jennifer; Kelly, Niamh
Abstract : This paper considers the attitudes and behaviours of university language lecturers and their students regarding the use of the L1 in the higher education L2 classroom. A case study of one Irish higher education institution was carried out and qualitative interviews conducted with six lecturers in Japanese and six in German. The results indicated widespread support among the participants for the judicious use of the L1 in limited instances, particularly where it can facilitate a reduction in cognitive overload and learner anxiety by, for example, the explanation of complex terminology, concepts and grammatical structures, as well as aiding in the creation of a relaxed classroom environment. Implications for the language classroom and for this field of research are considered.